PENGARUH PEMBELAJARAN CAI-KONTEKSTUAL TERHADAP KEMAMPUAN BERPIKIR MATEMATIK DAN KARAKTER MAHASISWA - Nanang Nanang (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2017)
The purpose of this study to determine the effect of CAI-Contextual learning of the ability to think mathematically and character of the student teacher participants of the course Capita Selecta Mathematical SMA. The population in this study is the fourth semester students of Mathematics Education STKIP Garut academic year 2015/2016. Selection of the sample by means of random sampling, the students obtained grade B as an experimental class and class A as the control class. Experimental class taught by CAI-Contextual learning, whereas the control class was taught by conventional learning. Retrieval of data obtained by the test method to get the data value of the initial knowledge of mathematics students and Mathematical Thinking Skills as well as the method of questionnaire to measure student character, and then analyzed with the average difference. The results showed that there are differences in the ability to think mathematically and character class students experiment with the control class. Since the average mathematical thinking skills and character students experimental class is bigger than the control class, it can be concluded that the CAI-Contextual learning positively affects the ability to think mathematically and character of the student teacher participants of the course Capita Selecta Mathematical SMA.